The effect of rice husk ash and metakaolin as partial cement replacement in concrete towards corrosion resistance - Nurul Amarlina, Sharifudin (2018)
Pozzolanic materials are natural or artificial materials produced from combustion of the waste. In Malaysia, the utilization of the pozzolanic materials has been widely used in concrete construction which used as a partial replacement material in concrete. In this study, Rice Husk Ash (RHA) and Metakaolin (MK) were utilized as pozzolanic material in concrete. Rice husk ash is a by-product material obtained from the combustion of rice husk which consists of non-crystalline silicon dioxide with a high specific surface area and high pozzolanic reactivity. It also has demonstrated significant influence in improving the mechanical and durability properties of concrete. Other than that, metakaolin is a new active mineral admixture used in cement concrete product and it also has a good effect on the mechanical properties of cement. The behaviours of RHA + MK performance in improving corrosion resistance, water absorption and compressive strength due to the different percentage of partial cement replacement in concrete were assessed in this study. Besides, the percentage of concrete containing rice husk ash and metakaolin were 10%, 20%, and 30% and their combinations as the partial replacement of cement in concrete was (1:1 ratio). Next, water absorption test was done to determine the percentage of water absorption in the concrete and the test for corrosion resistance was accelerated corrosion test with impressed voltage. From the result, it was found that the incorporation of rice husk ash and metakaolin have the potential to be used as partial cement replacement in concrete to reduce the water absorption and increase the corrosion resistance. Therefore, rice husk ash and metakaolin can be used as partial cement replacement in concrete and the optimum percentage of partial cement replacement was up to 20% of rice husk ash and metakaolin in concrete.